The challenge of early glomerular filtration rate decline in response to antihypertensive treatment and chronic kidney disease outcomes. Issue 2 (6th November 2020) - Signorini, Lorenzo; Zaza, Gianluigi; Gambaro, Giovanni
Abstract: Hypertension and chronic kidney disease (CKD) are closely linked pathological processes. Combating high blood pressure (BP) is an essential part of preventing CKD progression and reducing cardiovascular (CV) risk. Data from recent randomized controlled trials on patients at high CV risk showed the beneficial effects of intensive action to meet BP targets on mortality related to CV disease. The impact of meeting such targets on renal function is still unclear, however, particularly for patients with CKD. This issue has been the object of several post hoc analyses because lowering BP definitely has a nephroprotective role, but the early decline in glomerular filtration rate (GFR) associated with antihypertensive therapies and strict BP targets is still a concern in nephrology clinical practice. The present review discusses the results of studies on this topic, focusing specifically on the clinical significance of early GFR decline in response to treatment with angiotensin-converting enzyme inhibitor/angiotensin receptor blocker, or to different BP targets, in terms of renal and CV outcomes, and how this tips the balance towards continuing or discontinuing antihypertensive therapy.